Emotional intelligence and academic resilience among international students in cross-cultural contexts - Mugabekazi, Joie Claire (Journal of International Students, 2026)
This paper explores emotional intelligence (EI) as a coping resource for international PhD students, drawing on my experiences studying in China. Using Goleman’s EI framework, this study examines how self-awareness, self-regulation, intrinsic motivation, empathy, and social skills support my adaptation to academic pressures, cultural challenges, and mental well-being. This reflection highlights the role of EI in fostering resilience, emotional regulation, and supportive relationships amid stress and isolation. The findings highlight the significance of EI in promoting academic persistence and psychological adjustment among international students. Practical recommendations suggest integrating EI development into university support services. This research bridges theoretical insights with personal experiences, contributing to an understanding of the impact of emotional intelligence in higher education contexts.